Acute Effects of a Week of Stochastic‐Random Whole‐Body Vibration on Manual Ability Performance in Healthy Subjects: A Preliminary Pilot Study. - Alguacil Diego, Isabel Mª.; Martínez Piédrola, Rosa Mª.; Aguilera Rubio, Ángela; Gómez Alguacil, Miguel; Molina Rueda, Francisco; Banerjee, Baisakhi (BioMed Research International, 2025)
Aim: The aim of the study is to evaluate whether stochastic whole‐body vibration (WBV) can improve dexterity and manipulative capacity in healthy individuals using a conventional squat position over a short period (1 week). Introduction: Many pathologies specifically affect fine motor dexterity. Numerous therapies are aimed at improving upper extremity functionality. In this context, WBV appears to represent a significant breakthrough in the field of rehabilitation. The mechanical vibration signals activate sensory receptors (muscle spindles), triggering reflex muscle activation like the tonic vibration reflex. The random mechanoreceptor stimulation maintains continuous brain activation, increasing corticospinal excitability. Methods: Thirty‐eight healthy young volunteers were randomized to the WBV group (N = 19; 6 men, 13 women) or the control group (N = 19; 6 men, 13 women). The subjects in the WBV group performed one series of five consecutive repetitions of 60‐s unsynchronized WBV (Zeptoring, Scisen GmbH, Germany; mechanical vibration of 4 Hz and amplitude of 3 mm) with a 1‐min pause between administrations, three times a week. Baseline and 5 min after the intervention, preferred hand (PH), nonpreferred hand (NPH), both hands (BH), and assembly (A) of the Purdue Pegboard test were performed. Results: Student's t‐test showed a significant advantage in favor of the WBV group for NPH and BH compared to the control group. Among all variables, the NPH showed the most substantial improvement, with an increase of approximately 12% (p < 0.02), while BH improved by 8% (p < 0.01). Conclusions: Acute low‐frequency WBV in a squat position improves manual dexterity in healthy subjects. Future studies with larger sample sizes and diagnostic methods are needed to support these findings. Trial Registration: ClinicalTrials.gov identifier: NCT03289689